2001
DOI: 10.1093/emboj/20.4.672
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-C-mediated lymphangiogenesis promotes tumour metastasis

Abstract: Metastasis is a frequent and lethal complication of cancer. Vascular endothelial growth factor‐C (VEGF‐C) is a recently described lymphangiogenic factor. Increased expression of VEGF‐C in primary tumours correlates with dissemination of tumour cells to regional lymph nodes. However, a direct role for VEGF‐C in tumour lymphangiogenesis and subsequent metastasis has yet to be demonstrated. Here we report the establishment of transgenic mice in which VEGF‐C expression, driven by the rat insulin promoter (Rip), is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
683
2
9

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 848 publications
(717 citation statements)
references
References 52 publications
23
683
2
9
Order By: Relevance
“…25 For gastric tumors, as for many others, VEGF-C is considered the prominent inducer of tumor lymphangiogenesis. Consequently, a tumor therapy targeting VEGF-C would be particularly efficacious in the treatment of gastric tumor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…25 For gastric tumors, as for many others, VEGF-C is considered the prominent inducer of tumor lymphangiogenesis. Consequently, a tumor therapy targeting VEGF-C would be particularly efficacious in the treatment of gastric tumor.…”
Section: Discussionmentioning
confidence: 99%
“…for 10 min, and it protects DNA from degradation in 10% FBS and 10% newborn bovine serum at 37 1C for 12 h. Furthermore, we found that the optimal ratio of CaCO 3 nanoparticle to DNA is 15:1, and the maximal gene expression is observed 48 h after transfection. The CaCO 3 Abbreviations: PBS, phosphate-buffered saline; siRNA, small interfering RNA; VEGF-C, vascular endothelial growth factor-C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other models, expression of VEGF-C in breast cancer cells promoted growth of tumour-associated lymphatics (Skobe et al, 2001a), that were in some cases infiltrated with tumour cells , and metastatic spread to lymph nodes (Mattila et al, 2002). In a transgenic mouse model of pancreatic cancer, expression of VEGF-C in tumour cells led to extensive lymphangiogenesis associated with the tumours and metastases in draining lymph nodes (Mandriota et al, 2001). Expression of VEGF-D in tumour cells of a mouse xenograft model promoted formation of intratumoural lymphatics, angiogenesis, tumour growth and metastasis to lymph nodes ).…”
Section: Lymphangiogenic Signalling and Tumour Metastasismentioning
confidence: 99%